Overexpression of lncRNA SLC26A4‐AS1 inhibits papillary thyroid carcinoma progression through recruiting ETS1 to promote ITPR1‐mediated autophagy. Issue 17 (10th August 2021) - Peng, Dong; Li, Wenfa; Zhang, Bojuan; Liu, Xuefen
Abstract: Papillary thyroid carcinoma (PTC), accounting for approximately 85% cases of thyroid cancer, is a common endocrine tumour with a relatively low mortality but an alarmingly high rate of recurrence or persistence. Long non‐coding RNAs (lncRNAs) is emerging as a critical player modulating diverse cellular mechanisms correlated with the progression of various cancers, including PTC. Herein, we aimed to investigate the role of lncRNA SLC26A4‐AS1 in regulating autophagy and tumour growth during PTC progression. Initially, ITPR1 was identified by bioinformatics analysis as a differentially expressed gene. Then, Western blot and RT‐qPCR were conducted to determine the expression of ITPR1 and SLC26A4‐AS1 in PTC tissues and cells, both of which were found to be poorly expressed in PTC tissues and cells. Then, we constructed ITPR1‐overexpressing cells and revealed that ITPR1 overexpression could trigger the autophagy of PTC cells. Further, we performed a series of gain‐ and loss‐of function experiments. The results suggested that silencing of SLC26A4‐AS1 led to declined ITPR1 level, up‐regulation of ETS1 promoted ITPR1 expression, and either ETS1 knockdown or autophagy inhibitor Bafilomycin A1 could mitigate the promoting effects of SLC26A4‐AS1 overexpression on PTC cell autophagy. In vivo experiments also revealed that SLC26A4‐AS1 overexpression suppressed PTC tumour growth. In conclusion, our study elucidated that SLC26A4‐AS1 overexpression promoted ITPR1 expression through recruiting ETS1 and thereby promotes autophagy, alleviating PTC progression. These finding provides insight into novel target therapy for the clinical treatment of PTC.